TEMPAT MISTIS PUTRI ERIKA: PEMANFAATAN TIKTOK SEBAGAI MEDIA PROMOSI ‘WISATA MISTIS’ DI KOTA YOGYAKARTA - Oktaviani Tri Jumiatini; Zahrotus Saidah (Cakrawala - Jurnal Humaniora, 2022)
TikTok is a digital platform founded by ByteDance in 2016 in China. The development of TikTok has increased over years. In fact, TikTok is the most downloaded non-gaming application in 2020. This popularity has indirectly led to many content creators to produce various unique ideas, one of which is Putri Erika, a content creator who consistently presents horror content about mystical tourist attractions in Yogyakarta, namely through Tempat Mistis Putri Erika. By using qualitative methods, this research describes result based on observations, interviews with Putri Erika and Tim, and documentation. Based on the result, it can be concluded that Tempat Mistis Putri Erika is the result of observations about the behavior of the Indonesian people who like things related to the mystical. Certainly, this cannot be separated from the history of their beliefs, namely animism and dynamism. And from the results of these observations, the idea to explore mystical places emerged especially in the Yogyakarta area, which is popular place for culture, values and mysticism, As for the process, media is needed to promote and persuade Tempat Mistis Putri Erika, namely Tiktok media. So, if sorted, the content of Tempat Mistis Putri Erika is the result of technological social construction or also known as Social Construction of Technology (SCOT). Based on these findings, this research is also expected to provide benefits, especially for activists in the field of content creators, both in terms of strategy and in terms of media utilization so that it can be used as evaluation material to create unique and interesting content.